Analisa kelayakan kredit usaha mikro berjalan pada perbankan dengan metode naive bayes - Rita Retnosari (Universitas Serang Raya, 2021)
The development of information systems currently has a very influential on human life, especially in the world of work and in the education of information and communication technology lessions. Almost all business activities in banking now require an information system. Information syatem can help companies in the banking world to determine their performane in predicting the credit worth hiness of micro-enterprises to run optimally and efficiently. To connect to the internet, a company must integrated with one of the information system services by running on system sofware, which is provided according to the needs of the banking world. Data mining classification can be done using the naive bayes algorithm for knowledge result that are easy to understand and easy to understand. How ever, if the use of information systems in micro business credit performance is running more and more, there will be inaccuracy in a business credit, so customers will not believe in the performance of running micro business loans.